n-3=-n+3

Simple and best practice solution for n-3=-n+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-3=-n+3 equation:


Simplifying
n + -3 = -1n + 3

Reorder the terms:
-3 + n = -1n + 3

Reorder the terms:
-3 + n = 3 + -1n

Solving
-3 + n = 3 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
-3 + n + n = 3 + -1n + n

Combine like terms: n + n = 2n
-3 + 2n = 3 + -1n + n

Combine like terms: -1n + n = 0
-3 + 2n = 3 + 0
-3 + 2n = 3

Add '3' to each side of the equation.
-3 + 3 + 2n = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 2n = 3 + 3
2n = 3 + 3

Combine like terms: 3 + 3 = 6
2n = 6

Divide each side by '2'.
n = 3

Simplifying
n = 3

See similar equations:

| 8a-2a= | | 9w=6.3 | | y=2/3(11)+4 | | -15=(5q-10)-5q | | 2(w-4)=26 | | (5y-7)^-4/3((5y-7)-3) | | 5x-22=3x+16 | | -1.5(x-2.25)=-10.55 | | -3p+4=-9(5p-10)-2(-5-5p) | | 1/8(a+3)=1/4(9-a) | | (n+3)5=3(2n-1) | | 6x6/7 | | 2/3G=-5/2 | | (6/x-4)/(2x-3)=0 | | 10y-6=4y+8 | | 8h=26 | | 7-(2z-5)=6-3z | | 2/3y+v=x | | v-9=214 | | 16+8x=25+15+3 | | -13x-13=2x-46 | | 220=4(-2+7x)+4 | | y=2/3(7)+4 | | -8(1+7m)=384 | | 0=4(4t^2+16t-7) | | 3.50+2.50x=25 | | -15+m/4=-11 | | -11n+16=-10n-5 | | -4(2-c)=12 | | -3(4r+-8)=-36 | | 49/98=a/112 | | 2/5+4/7 |

Equations solver categories